Contemporary feminist theories - Jackson, Stevi; Jones, Jackie, 1964- (Edinburgh University Press, 1998)
Feminist theory has grown into a vast field. Feminist writers, thinkers, and activists have produced an often bewildering body of knowledge concerned with difference and diversity, identity and inequality, ethnicity, race, and class, as well as gender. Despite its growing influence, however, no single comprehensive text encompasses the past, present, and future of feminist theory. Contemporary Feminist Theories was inspired by a dissatisfaction with existing introductions, which often fail to fully track change and capture diversity within feminist thought. The volume draws on the expertise of a range of Western feminists in order to reflect the breadth of feminist theory as well as shifts within it. Each chapter maps the development of feminist thought in a particular area over time, and suggests future directions. Reflecting the diversity of feminist theory in fields from literature and linguistics to science and politics, this multi-disciplinary map of feminist thinking is an ideal classroom text.